Rastin partnership accounting part I: general procedure. Issue 4 (8th July 2019) - Bidabad, Bijan; Allahyarifard, Mahmoud; Sherafati, Mahshid
Abstract : Purpose: This paper aims to explain a new system of accounting for partnership financing that applies in Rastin profit and loss sharing banking. In this system, the interest rate is not used in calculations and accounting, and instead, the "time value" of capital based on the amount and duration of the partnership is used. Design/methodology/approach: Rastin Partnership Accounting principles have been founded on off-balance-sheet items and on the basis of the institutions' obligations to the depositors and receivers of financial resources, and they are in compliance with the nature of the financial intermediary activity (a partnership of depositor in the yields of the fund receiver via the bank). Findings: The distribution of profit among stakeholders (including workforce and capital owners) is accomplished according to the share of each beneficiary in the created value added. In this regard, Euler's theorem, as the best mathematical-economic innovation for distribution of income is applied. Research limitations/implications: This system is novel, and it is required to be more elaborated for further practical development and adjustment. Practical implications: In this accounting system, the return of the partnership is distributed among sharers based on the amount and duration of their partnership. The penalty for delay in payment is calculated from the amount of the incurred loss due to negligence or blameworthy of the undertaker and not upon a penalty interest rate. Social implications: Interest rate as an essential factor in conventional accounting is not usable in Islamic banking and other similar institutions that work based on partnership, such as mutual funds and saving and loan associations. The proposed system removes this shortage and is fairer than the conventional accounting. Originality/value: Approach of this accounting system is fully different from the conventional accounting because of intrinsic characteristics of the intermediary role of financial partnership institutions and Islamic banks.